Pointing fingers and holding hands: Effects of collaborative and confrontational NPO approaches on households' consumption and donation decisions. (8th February 2022) - Arnold, Nicholas
Abstract: Nonprofit organizations (NPOs) seek to influence corporate responsibility practices by pursuing either collaborative or confrontational approaches toward companies. In doing so, they frequently attempt to influence households' perceptions of companies and, by extension, their consumption decisions. To what extent NPOs adopting varying approaches toward companies are successful in affecting households' perceptions and decisions, however, remains underexamined. Furthermore, how NPOs' choice of approach impacts households' perception of and donation behavior toward NPOs remains a largely open question. In this contribution, we investigate these issues by means of an experimental approach. The results of our study indicate that both confrontational and collaborative approaches by NPOs exert a significant effect on households' perceptions of companies and their consumption intentions. Somewhat paradoxically, while confrontational approaches exert stronger effects on households' perceptions of companies and their consumption behavior, collaborative approaches are viewed as more legitimate by households, thus garnering more support in the form of donations.